Correlation Between Car Size, Weight, Power, and Vowel Quality in Model Names - Stolarski, Łukasz (Studia Anglica Posnaniensia, 2020)
This paper focuses on the practical application of the theory of sound symbolism in brand name development and examines which of the two phonetic dimensions of vowel articulation, the vertical articulatory scale or the horizontal one, is utilised to a higher degree in communicating the size of a vehicle to customers. The methodology used in previous studies on size-sound symbolism did not make it possible to separate the two aspects of vowel articulation. In the present paper, these dimensions were categorised by the use of quantitative methods. Each Received Pronunciation vowel was assigned a numerical value separately on both scales. Then, the correlations between the values obtained for horizontal and vertical articulation of the vowels present in the names of cars sold in Great Britain and the physical attributes of the respective vehicles such as size, weight, and power were calculated. The final results reveal that it is only the vertical scale of vowel articulation which is utilised to signal the physical characteristics of the vehicles examined in this project. Although these findings refer directly to British English, they may also have more universal implications for the theory of magnitude sound symbolism.